ANALYSIS OF SERVICE QUALITY IN PIZZA HUT SUDIRMAN PEKANBARU RIAU - Maya Rachman; Indra Safri (UIR Press, 2018)
Customer satisfaction is the feeling of pleasure or disappointment of someone who emerges after comparing the performance (result) of the product to the expected performance. Customer satisfaction is influenced by the perception of various qualities, both services and products. One of the factors that determine customer satisfaction is customer perceptions of service quality that focus on five dimensions of service quality, ie Physical Evidence, Reliability, Responsiveness, Assurance and Empathy. One of the restaurant organization that has good customer satisfaction is Pizza Hut Sudirman Pekanbaru Riau. This study aims to determine and analyze how influential customer satisfaction for Pizza Hut retorance on the level of satisfaction perceived by customers who buy or consume pizza Hut Sudirman Pekanbaru Riau. The type of research used is the type of descriptive research, namely the description of the reality that exist in the field. Methods of data collection is done by interview, questionnaire questionnaire s(questionnaire), observation, documentation. And use 3 purposive sampling technique that is for sampling at 7 employees, census technique for sampling at 1 Manager 1 assistant Manager 1 Sift Leader and use isedental sampling for sampling on 30 consumers. The results of the 5 indicators are Very Important. The author's suggestion is to improve the quality of customer satisfaction by fixing the five independent variables that are considered less than the maximum